GAY SUBJECTIVITY IN ANTONIO BOTTO'S POETRY - Outeiro Fernandes, Maria Lucia [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2018)
By seeking to understand Antonio Botto's absence in the canon of Portuguese lyric poetry of the 20th Century, this paper proposes some reflections on the aesthetic aspects of his work. In addition to this objective, we also intend to discuss the bond created between Aestheticism and Decadentism in his dramatic poetry - which causes tension with humanism or literary vitalism - in order to better express gay subjectivity and form a queer identity.
Keywords: Antonio Botto; portuguese poetry; dramatic poetry; gay subjectivity; queer identity